NT server - Kenneth L Spencer (Prentice Hall PTR, 1996)
Installation of NT server; Server configuration and management; Network configuration and management; User management; file systems; Client configuration and management; Services for macintosh; Printer use and management; disaster preparedness and management; Tuning NT server and networks; Security.